Exploring pathways in hospitality and tourism [videorecording] - Hayward, Nick; Tosi, George; Robbio, Michael De; Video Education Australasia (Australia : Video Education Australasia, 2008)
The hospitality and tourism industry is a strong, stable and expanding sector of the Australian workforce, employing more than half a million people. In this program we examine some of the amazing apprenticeships, traineeships and other training qualifications that lead to careers in this dynamic industry.
Executive produce, Simon Garner
Keywords: Hospitality industry -- Australia; Tourism -- Australia; Tourism -- Employees -- Training of -- - Australia